Hollow Mesoporous Carbon Spheres for High Performance Symmetrical and Aqueous Zinc-Ion Hybrid Supercapacitor - Chen, Sihan; Yang, Gaoqi; Zhao, Xiaojuan; Wang, Nengze; Luo, Tingting; Chen, Xu; Wu, Tianci; Jiang, Shijie; van Aken, Peter A.; Qu, Shile; Li, Tao; Du, Liang; et al. (Frontiers in Chemistry, 2020)
Zinc–ion hybrid supercapacitors are a promising energy storage device as they simultaneously combine the high capacity of batteries and the high power of supercapacitors. However, the practical application of Zinc–ion hybrid supercapacitors is hindered by insufficient energy density and poor rate performance. In this study, a symmetrical zinc–ion hybrid supercapacitor device was constructed with hollow mesoporous-carbon nanospheres as electrode materials, and aqueous ZnSO4 adopted as an electrolyte. Benefiting from the mesoporous structure and high specific area (800 m2/g) of the hollow carbon nanospheres, fast capacitor-type ion adsorption/de-adsorption on both the cathode and the anode can be achieved, as well as additional battery-type Zn/Zn2+ electroplating/stripping on the anode. This device thus demonstrates outstanding electrochemical performance, with high capacity (212.1 F/g at 0.2 A/g), a high energy density (75.4 Wh/kg at 0.16 kW/kg), a good rate performance (34.2 Wh/kg energy density maintained at a high power density of 16.0 kW/kg) and excellent cycling stability with 99.4% capacitance retention after 2,500 cycles at 2 A/g. The engineering of this new configuration provides an extremely safe, high-rate, and durable energy-storage device.